EP821 Short-term safety and outcomes of HIPEC in ovarian cancer patients. (1st November 2019) - Cruz, A; Martins, D; Monteiro, AR; Peyroteo, M; Pereira, B; Coelho, F; Martins, A; de Sousa, A; Pereira, D; Faria, F
Abstract : Introduction/Background: Hyperthermic intraperitoneal chemotherapy (HIPEC) for ovarian cancer patients with peritoneal metastasis remains controversial concerning patient selection, safety, efficacy and costs. A randomized phase 2 trial failed to show survival superiority for interval cytoreductive surgery (ICRS) with HIPEC compared to surgery alone. HIPEC group had more anemia and creatinine elevation. Recently, a phase 3 trial showed longer recurrence-free and overall survival for HIPEC group, without increasing toxicity. We aimed to evaluate safety and efficacy of ICRS with HIPEC. Methodology: Retrospective cohort of patients submitted to ICRS and HIPEC with cisplatin 50 mg/m 2, from 2013 to 2018. Data were analyzed using descriptive statistics and survival was estimated by Kaplan-Meier method. Results: Thirty patients were included, median age was 60 years (IQR, 15) and all had ECOG <2. Stage was IIIC (FIGO, 2014) in 56.7% (17/30). Median peritoneal cancer index was 11 (IQR, 15). After surgery, 66.7% (20/30) were admitted to the intensive-care unit (ICU), and 33.3% (10/30) to the high-dependency unit (HDU). Mean APACHE II and SAPS II score was 9.7 and 25.5, respectively. Ten percent (3/30) needed invasive mechanical ventilation, despite 23.3% (7/30) developed respiratory failure. None (0/30) had hemodynamic instability or renal failure. Anemia occurred in 73.3% (22/30); mean lower hemoglobin level was 10.5 (±1.3) g/dL. Median length of stay in ICU/HDU was 2 days (IQR, 1) and in the hospital was 11 days (IQR, 5). One patient needed reoperation due to gastrointestinal leakage and peritonitis; and one had right femoral nerve neuropraxia. There was no readmission to ICU/HDU or in-hospital mortality. After a median follow-up of 14 months, 40% (12/30) progressed and 33.3% (10/30) died. Median PFS was 8 months (95% CI 4.7–11.3) and OS was 10 months (95% CI 0.7–19.3). Conclusion: In our cohort HIPEC was a safe technique. Long-term outcomes suggest the benefit of this procedure in the management of well-selected patients. Disclosure: Nothing to disclose.